HRM and green innovation of manufacturing firms in Australia - AHMED, UMAIR; MOZAMMEL, SOLEMAN; ZAMAN, FAZLUZ (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Following the footsteps of resource-based view theory, the present study attempted to examine HRM and its impact on green innovation followed by the interplay of green transformational leadership. The study collected triadic data by using a survey questionnaire from 185 small and medium manufacturing firms in New South Wales, Australia. Results from the data analysis suggest that HRM prospects of green ability and motivation have a significant relationship with green innovation. Accordingly, the results also indicated a significant relationship between green transformational leadership and green innovation. Overall, the present research has advanced understanding of green GRM and green leadership to utilize personnel prospects to further green innovation effectively. RESUMEN Siguiendo los pasos de la teoría de la visión basada en recursos, el presente estudio intentó examinar la gestión de recursos humanos y su impacto en la innovación ecológica seguida de la interacción del liderazgo transformacional. Se recopilaron datos triádicos mediante el uso de un cuestionario a 185 pequeñas y medianas empresas manufactureras en Nueva Gales del Sur, Australia. Los resultados del análisis de datos sugieren que las perspectivas de la gestión de recursos humanos de capacidad y motivación ecológicas tienen una relación significativa con la innovación ecológica. En consecuencia, los resultados también indicaron una relación significativa entre el liderazgo transformacional verde y la innovación. En general, la presente investigación ha avanzado la comprensión del GRM verde y el liderazgo para utilizar las perspectivas del personal y promover la innovación verde de manera efectiva.